2010
DOI: 10.1002/ps.2035
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Rhynchophorus ferrugineus adults to selected synthetic palm esters: electroantennographic studies and trap catches in an urban environment

Abstract: This study supports the application of the mass trapping implemented with synthetic palm esters as a potential tool for the management of RPW populations to protect ornamental palms in urban environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 16 publications
4
49
0
Order By: Relevance
“…Pest management in clover seed production would therefore greatly benefit from development of odor-based strategies for weevil control. For instance, mass-trapping using aggregation pheromones, sometimes in combination with host plant volatiles (Guarino et al, 2011), has been successful for other weevil species (Cross et al, 2006;Rhino et al, 2010;Smith, 1998). In addition, plant compounds from both hosts and non-hosts might act as anti-attractants, like in many species of bark beetles (Andersson et al, 2010;Zhang and Schlyter, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Pest management in clover seed production would therefore greatly benefit from development of odor-based strategies for weevil control. For instance, mass-trapping using aggregation pheromones, sometimes in combination with host plant volatiles (Guarino et al, 2011), has been successful for other weevil species (Cross et al, 2006;Rhino et al, 2010;Smith, 1998). In addition, plant compounds from both hosts and non-hosts might act as anti-attractants, like in many species of bark beetles (Andersson et al, 2010;Zhang and Schlyter, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found ethyl acetate synergizing the lure-food bait attraction of RPW (Oehlschlager, 1998;El-Sebay, 2003;Al-Shagag et al, 2008;Guarino et al, 2011;Al-Saoud, 2013;Giblin-Davis et al, 2013;Vacas et al, 2014Vacas et al, , 2017. For example, in a latest study using food-baited wet bucket trap and a commercial product, Weevil Magnet™, Al Saoud (2013) showed that mean monthly RPW trap catches from ethyl acetate and lure combination were ~1.6 times higher than the traps without ethyl acetate.…”
Section: Lure and Ethyl Acetatementioning
confidence: 99%
“…The use of ethyl acetate as co-attractant along with lure and food bait is widely known, practiced and recommended (Oehlschlager et al, 1993;Hallett, 1996;Hallett et al, 1999;Faleiro and Kumar, 2008;Al-Saoud et al, 2010;Roda et al, 2011). However, discovery of the other key odorants synergizing attraction will help in development of standardized and optimized synthetic synergist or a blend to optimize kairomonal effect without using plant material (Guarino et al, 2011;Vacas et al, 2014).…”
Section: Food Baitmentioning
confidence: 99%
“…Presently, the control methods used include prompt destruction of infested plant material (Kurian and Mathen 1971), prophylactic treatment of cut wounds (Pillai 1987), deep cutting to remove growing points of off-shoots (unwanted growths from the trunk) (Azam and Razvi 2001), endotherapy measures (el-Ezaby 1997b;Hernandez-Marante et al 2003), predacious measures (Abraham and Kurian 1973), pathogens (Salama et al 2004;Gómez Vives et al 2008), insecticides (Barranco et al 1998;, microwave plant treatment (Sansano Javaloyes et al 2008;Massa et al 2011), chemosterilization (Ramachandran 1991) and mass trapping based on pheromones (Vidyasagar et al 2000). Recently, Guarino et al (2011) showed that mass trapping implemented with palm esters is an important tool for the management of the RPW population and for preventing infestation of ornamental plants in urban environments.…”
Section: Introductionmentioning
confidence: 99%